Titanium : industrial base, price trends, and technology initiatives - Sŏng, So-mi (Rand Corporation monograph series., 2009)
Between 2003 and 2006, the price of titanium more than doubled. The authors attempt to answer four primary questions: What triggered this price surge? What are titanium's future market prospects and emerging technologies? What are the implications for the production cost of future military airframes? How might the Department of Defense mitigate the economic risks involved in the titanium market?